An Electroactive Oligo‐EDOT Platform for Neural Tissue Engineering. (14th August 2020) - Ritzau‐Reid, Kaja I.; Spicer, Christopher D.; Gelmi, Amy; Grigsby, Christopher L.; Ponder, James F.; Bemmer, Victoria; Creamer, Adam; Vilar, Ramon; Serio, Andrea; Stevens, Molly M.
Abstract: The unique electrochemical properties of the conductive polymer poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) make it an attractive material for use in neural tissue engineering applications. However, inadequate mechanical properties, and difficulties in processing and lack of biodegradability have hindered progress in this field. Here, the functionality of PEDOT:PSS for neural tissue engineering is improved by incorporating 3, 4‐ethylenedioxythiophene (EDOT) oligomers, synthesized using a novel end‐capping strategy, into block co‐polymers. By exploiting end‐functionalized oligoEDOT constructs as macroinitiators for the polymerization of poly(caprolactone), a block co‐polymer is produced that is electroactive, processable, and bio‐compatible. By combining these properties, electroactive fibrous mats are produced for neuronal culture via solution electrospinning and melt electrospinning writing. Importantly, it is also shown that neurite length and branching of neural stem cells can be enhanced on the materials under electrical stimulation, demonstrating the promise of these scaffolds for neural tissue engineering. Abstract : Tunable block co‐polymers based around homogenous oligomers of the conjugated polymer PEDOT (oligoEDOT) are used to generate versatile biomaterial scaffolds for neural tissue engineering. This polymer platform provides a high level of structural modularity and control, facilitating the fabrication of complex 3D architectures and controlled electrical stimulation of neural stem cells.